Response of different genotypes and their cross combinations to anther culture in Ethiopian mustard (Brassica carinata A. Braun) - Shitole Ajit Mohanrao; Vedna Kumari (Journal of Oilseed Brassica, 2026)
The effects of seven genotypes and their cross combinations, two basal media i.e. B5 and MS, two different sucroseconcentrations i.e. 3% and 4% and three combinations of hormones viz., HM1, HM2 and HM3 and their interactions oncallus inductions frequency in Brassica carinata were analyzed by using CPCS software. Mean sum of squares due toall factors were significantly revealed the effects of genotypes, media, hormones, sucrose and their interactions oncallus induction frequency. Out of all factors and their interactions, the genotype P-51 performed better in B5 mediumsupplemented with HM2 (0.2mg/l BAP + 2.0 mg/l NAA) and 3% sucrose concentration for high callus induction frequency.